Investigating Pedagogical Competences of PPG Students in Designing and Implementing English Language Learning Videos: - - Rahmawati Upa; Sri Damayanti; Reski Yusrini Islamiah Yunus (JOLLT Journal of Languages and Language Teaching, 2026)
Teacher professional competence is a critical element in ensuring effective teaching and learning, particularly in the context of English as a foreign language. In the In-service Teacher Professional Education Program (PPG Guru Tertentu), participants are expected not only to prepare lesson plans but also to translate them into pedagogically sound practices, including the development of English learning videos. This study therefore aimed to analyse the pedagogical competence of PPG Guru Tertentu students majoring in English by examining the quality of their lesson plan development and the implementation of pedagogical competence in teaching practices documented through instructional videos. Employing a qualitative descriptive design, data were collected from twenty participants’ lesson plans and teaching videos The data were analysed thematically following Miles and Huberman’s interactive model through data reduction, data display, and conclusion drawing, with triangulation between document analysis and video observation. The findings show that while participants produced lesson plans that met administrative requirements, learning indicators were often too general and only partially aligned with Bloom’s Taxonomy, and assessment tended to focus on recall. The videos further revealed inconsistencies between planning and practice, simplification of student-centred activities, limited creativity in media utilization, and a strong reliance on unmodified YouTube videos. These results suggest that pedagogical competence is developing but remains uneven, particularly in operationalizing objectives, maintaining alignment between lesson plans and classroom practice, and designing authentic assessments.